Fostering Child-Friendly Schools Through Strengthened School-Parent Partnerships: Addressing Violence and Bullying Against Female Students in Senior High Schools - Sonya Veronika Nggauk; Lucky Endrawati; Dhia Al Uyun (STAI Hubbulwathan Duri, 2025)
Creating a child-friendly school environment requires collaborative efforts between schools and parents, particularly in combating violence and bullying targeting female students. This study explores how school-parent partnerships can enhance student safety and foster inclusivity in senior high schools. Using a qualitative case study approach, research was conducted in three private senior high schools in Malang, Indonesia (SMA A, SMA B, and SMA C). Data collection methods included in-depth interviews, classroom observations, and document analysis involving principals, teachers, parents, and students. The findings indicate that strong school-parent collaboration significantly reduces gender-based violence, such as body shaming and sexual harassment. These partnerships improved communication, encouraged joint prevention efforts, and strengthened a shared sense of responsibility among stakeholders. A safer and more inclusive school climate emerged, positively impacting the well-being of female students. Effective engagement between schools and families plays a strategic role in establishing protective systems and promoting a respectful school culture. The study underlines the importance of gender-sensitive strategies and inclusive school policies in creating supportive learning environments. To ensure all students, particularly girls, feel protected, schools should strengthen communication with parents and involve them in safety initiatives. This research underscores the crucial role of school-parent collaboration in addressing gender-specific issues and advancing child-friendly educational spaces.